Perinatal outcome of stage-based management of fetal growth restriction in a government tertiary care hospital in Kerala, India - Rangarajan, Bhargavi; Karunakaran, Lalithambica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
BACKGROUND: Fetal Growth Restriction (FGR) is the largest contributing factor to perinatal morbidity, mortality and impaired neurodevelopment. This research strives to elucidate the perinatal outcomes of stage based management of fetal growth restriction using Obstetric Doppler and its association with maternal sociodemographic profile. METHODS: The research was conducted among 320 antenatal women whose Estimated Fetal weight was <10th centile. Periodic follow up with Doppler was done and managed as per the stage of FGR. Perinatal outcomes were compiled. RESULTS: The incidence of FGR in T.D Medical College, Alappuzha was 15.23%. SGA accounted for 47 %. The proportion of early and late onset FGR was 10.3% & 89.7% respectively. 57.18% of the newborns were admitted to NICU. The common complications were: Low birth weight – 47.8% ARDS – 21% , Sepsis – 9.6%, Necrotizing enterocolitis – 4%, Hyperbilirubinemia – 4.9%. The incidence of Neonatal death and stillbirth were 1.56% and 0.3% respectively. Mothers who were underweight, inadequate weight gain during pregnancy and short inter pregnancy interval had increased risks. Hypertensive disorders of pregnancy was the commonly associated medical condition. CONCLUSION: Prolongation of pregnancy even by one day results in 2% increased chances of survival of the newborn. Hence, it becomes imperative to identify the benign forms of FGR to prevent iatrogenic prematurity. Antenatal women should be screened for risk factors and undergo vigilant antepartum surveillance to bring about favourable perinatal outcome.